Zinc speciation in soils and relation with its concentration in fruits - Yaman, M; Okumus, N; Bakirdere, S; Akdeniz, I (Mrs Pushpa Agarwal, 2005)
An attempt was made to identify the zinc species in the soil that is most responsible for the plant-available Zn. The Zn concentrations of the fruit and soil samples were determined by using flame atomic absorption spectrometry (FAAS). The soil samples related to these fruits were digested and extracted by using different digestion and extraction reagents. The relation between the fruit-Zn and soil-extractable-Zn concentrations was examined in order to explain. the Zn uptake of fruit from soil. Probable chemical forms of Zn in soil were evaluated.
Keywords: speciation; zinc; soil; fruit; flame atomic absorption spectrometry